Failure to rescue as a source of variation in hospital mortality after hepatic surgery. Issue 7 (23rd April 2014) - Spolverato, G; Ejaz, A; Hyder, O; Kim, Y; Pawlik, T M
Abstract: Background: The mechanisms that underlie the association between high surgical volume and improved outcomes remain uncertain. This study examined the impact of complications and failure to rescue patients from these complications on mortality following hepatic resection. Methods: The Nationwide Inpatient Sample was used to identify patients who had liver surgery between 2000 and 2010. Hospital volume was stratified into tertiles (low, intermediate and high). Rates of major complications, failure to rescue and mortality following hepatic surgery were compared. Results: Some 9874 patients were identified. The major complication rate was 19·6 per cent in low-volume, 19·3 per cent in intermediate-volume and 16·6 per cent in high-volume hospitals ( P < 0·001). Most common major complications included respiratory insufficiency or failure (8·8 per cent), acute renal failure (4·2 per cent) and gastrointestinal bleeding (3·9 per cent), with each of these complications being less common in high-volume hospitals ( P < 0·050). The incidence of major morbidity following hepatectomy remained the same over the past decade, but failure to rescue patients from these complications decreased ( P = 0·011). The overall inpatient mortality rate following liver surgery was 3·2 per cent (3·8, 3·6 and 2·3 per cent for low-, intermediate- and high-volume hospitals respectively; P < 0·001). The rate of failure to rescue (death after a complication) was higher at low- and intermediate-volume hospitals (16·8 and 16·1 per cent respectively) compared with high-volume hospitals (11·8 per cent) ( P = 0·032). After accounting for patient and hospital characteristics, patients treated at low-volume hospitals who had a complication were 40 per cent more likely to die than patients with a complication in a high-volume hospital (odds ratio 1·40, 95 per cent confidence interval 1·02 to 1·93). Conclusion: The risk of death following hepatic surgery is lower at high-volume hospitals. The reduction in mortality appears to be the result of both lower complication rates and a better ability in high-volume hospitals to rescue patients with major complications. Abstract : High volume is associated with lower morbidity and mortality